If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3y + -24 = -39 + 8y Reorder the terms: -24 + 3y = -39 + 8y Solving -24 + 3y = -39 + 8y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-8y' to each side of the equation. -24 + 3y + -8y = -39 + 8y + -8y Combine like terms: 3y + -8y = -5y -24 + -5y = -39 + 8y + -8y Combine like terms: 8y + -8y = 0 -24 + -5y = -39 + 0 -24 + -5y = -39 Add '24' to each side of the equation. -24 + 24 + -5y = -39 + 24 Combine like terms: -24 + 24 = 0 0 + -5y = -39 + 24 -5y = -39 + 24 Combine like terms: -39 + 24 = -15 -5y = -15 Divide each side by '-5'. y = 3 Simplifying y = 3
| 12x^3+8x^2+27x+18=0 | | .5-2x=x | | 14x^2+19x=3 | | 28=2-5x | | ln(x-2)+(lnx)=0 | | 16+7y+-8= | | -2q^2+12q=0 | | a=29.5+-1.5625b | | 2ln(x)=ln(25) | | -12x^3-21x^2=-6x | | 32a+50b=944 | | -23x+7y=-3 | | 3.4e=3.74 | | 13x+72=-23 | | 4x*4= | | 2x^2-3x+4=3 | | 2a+3b=58.6 | | 1ax(2b+3c)= | | 30a+50b=944 | | 0=x^2+48x+398 | | 8(x+6)-35= | | 2x-3x+4=3 | | 2a+3b=58 | | 4log(2x-3)=14 | | (ab+a+b+6)+(3ab-b+c-6)= | | 4x^2+2x+15=0 | | 16t^2+40t+6=0 | | 64=20x-x^2 | | 2.5x+1.7=7.4e | | 3x-1-x-3=2 | | 2X-4X-4=10 | | (3x+7)(x-4)x=0 |